Comparison of pediatric antibiotherapy in primary care: Low vs. high prescribers - Aydın, Volkan; Kırmızı, Neriman İpek; Ataç, Ömer; Akıcı, Narin; Akıcı, Ahmet (Wiley, 2021)
[Abstract Not Available]
Keywords: Primary Care; Antibiotherapy; Pediatric